Odpowiedzi

Najlepsza Odpowiedź!
  • Zuma
  • Rozwiązujący
2010-04-14T23:06:16+02:00
A) -4x + (5x - 2y +3) = -4x + 5x - 2y + 3 = x - 2y + 3
b) (3a + 2b) + (3a + b +1) = 3a +2b + 3a + b + 1 = 6a + 3b + 1
c) 16x - (9x + 2y - 7) = 16x - 9x - 2y + 7 = 7x - 2y +7 (to zadanie jest dobrze, ponieważ gdy przed nawiasem stoi minus to każdy znak w nawiasie zamienia się na przeciwny)
d) (4a + 7b) + (2a + 3) + (a + 2b) = 4a +7b + 2a + 3 + a + 2b = 7a + 9b + 3
2010-04-14T23:06:25+02:00
A) x-2y+3
b) 6a+3b+1
c) 7x-2y+7
d) a+5b=3
a+5b-3
2010-04-14T23:09:40+02:00
A) -4x + (5x - 2y +3) =-4x+5x-2y+3=x-2y+3
b) (3a + 2b) + (3a + b +1)=3a+2b+3a+b+1=6a+3b+1
c) 16x - (9x + 2y - 7)=16x-9x-2y-7=7x-2y-7
d) (4a + 7b) = (2a + 3) + (a + 2b)=4a+7b=2a+3+a+2b=4a+
7b=3a+2b+3


pozdr